(3MOjbI GdCRgGQ hMbjbI GdGaJNGQ aj eOM GdfHi GdeNJGQs - (3GHf MGRe GdbQWGLfjs
(3ChdgG (B:s
(3HYjfjc bd Cf RQJ CaVd hUd baGfjc ef PcQi MHjH hefRd s
(3BNQgG (B:s
(3hdhSeYJg YUe WhO CeGdgG aCfRd ef GdYUe ef cd fRd s
(3GdeNWhW YHGQI Yf bUjOIs
(3LYd GdeDda CYLGRgG ef eYdbI GeQD GdbjSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(1 / 3717) s
Keywords: (3GdCOHs